Using Emoji in WhatsApp among the Students of Technical Education and Training Institutions in Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Using emoji is growing among people following the recent prevalent use of paralinguistic cues through computer-mediated communication. However, researches on proficiency and knowledge level, rating of advantages and disadvantages of emojis on WhatsApp in Tanzania are still scarce. Therefore, this study specifically determined emojis’ proficiency among TET students; perception of TET students towards advantages and disadvantages of using emojis; and it as well determined influence of demographic characteristics on the use of emojis among TET students. This study was approached quantitatively based on descriptive and explanatory survey design. Data were gathered using questionnaire from TET students sampled using stratified simple random technique from November to December, 2022. The collected data were analysed using Descriptive Statistics and Multiple Linear Regression. The findings indicate that, surveyed TET students had an average proficiency level in using emoji on WhatsApp. Furthermore, the TET students perceived the use of emoji in WhatsApp as more advantageous than being disadvantageous.  Some of the demographic information (i.e. gender, marital status, original home, and employment status) tested in this study had statistically significant and positive influence on use of emoji in WhatsApp. The Level of education pursued and age had statistically significant and negative influence on use of emoji in WhatsApp. The professionals of digital communication skills should continue to advocate use of emoji in order to improve the level of proficiency of the TET students for them to continue benefiting the advantages of the emoji in WhatsApp.